Organ-Size Regulation in Mammals - Penzo-Méndez, Alfredo I. (Cold Spring Harb Perspect Biol, 2015)
The control of organism and organ size is a central question in biology. Despite the attention it has received, our understanding of how adult organ size is determined and maintained is still incomplete. Early work has shown that both autonomous and regulated mechanisms drive vertebrate organ growth, and both intrinsic and extrinsic cues contribute to organ size. The molecular nature of organ-size determinants has been the subject of intense study, and major pathways, which underlie cell interactions controlling cell compartment size, have been identified. In this work, we review these data as well as the future perspectives of research in this important area of study.